Detección del virus del Dengue, Chikungunya y Zika en pacientes con síndrome febril en el departamento de Piura, Perú - Tantalean Yépez, Jorge Derek (2018)
Background: Arboviral diseases has reemerged in the last years affecting primarily the coast of Peru. Piura is an endemic region of Dengue, where the recent appearance of Chikungunya (CHIKV) and Zika (ZIKV) has been renewed. Aim: To assess the presence of DENV, CHIKV, and ZIKV in serum samples of patients with acute febrile illness in a locality of Piura, Peru and describe associated clinical features. Methodology: Descriptive cross-sectional study, sampling was done for convenience where it was obtained a total of 496 serum samples from patients with acute febrile illness were collected from 18 primary care centers. All samples were analyzed via real-time RT-PCR to detect DENV, CHIKV, and ZIKV. In addition, positive samples for DENV were also processed for serotypes 1 to 4 classification via RT-PCR. Results: DENV was the most common arbovirus detected in 170/496 (34.3%), followed by ZIKV in 39/496 (7.9%) and CHIKV in 23/496 (4.6%). Among the 170 samples positive for DENV, serotype 2 was the most predominant type present in 97/170 (57.1%) of samples, followed by the serotype 3 in 9/170 (5.3%). Headaches, muscle pain, and joint pain were the most common symptoms associated with fever in patients with DENV and ZIKV. No symptoms predominance was observed in patients with CHIKV. Conclusions: DENV is considered the most frequent arbovirus in Peru and the number of cases has increased dramatically in the last 5 years. However, it is not the only arbovirus that circulates along the northern coast of Peru. It has also been determined the presence of ZIKV and CHIKV in our population, which may suggest the circulation of other arboviruses that have not been detected.